Comparison of Zinc Plus Probiotics Therapy versus Probiotics Alone for Treatment of Acute Diarrhea in Children - Ijaz, Amina; Sheikh, Umer; Iftikhar, Sabika; Ahmad, Saed Aftab; Abbas, Amna (Indus Journal of Bioscience Research, 2025)
Background: Acute diarrhea is a major cause of morbidity in children under five years of age, particularly in developing countries. Objective: To compare the efficacy of zinc plus probiotics therapy versus probiotics alone in the treatment of acute diarrhea in children. Methods: This randomized controlled trial was conducted at the Department of Pediatrics, Hameed Latif Hospital, Lahore, from January 2025 to May 2025. A total of 80 children aged 3–60 months with acute diarrhea were enrolled and randomly allocated into two groups: Group ZP (zinc plus probiotics, n=40) and Group P (probiotics only, n=40). Group ZP received oral zinc (20 mg/day) for 10 days along with Bacillus clausii probiotics for 5 days, while Group P received probiotics alone. Outcomes measured included duration of diarrhea after treatment, total hospital stay, and recovery within five days. Results: The mean duration of diarrhea after treatment was significantly lower in Group ZP (28.4 ± 13.6 hours) compared to Group P (39.7 ± 18.9 hours) (p=0.004). The mean hospital stay was also shorter in Group ZP (2.6 ± 0.8 days) compared to Group P (3.3 ± 1.1 days) (p=0.002). Recovery within five days was achieved in 90.0% of children in the zinc plus probiotics group versus 72.5% in the probiotics-only group (p=0.04). Conclusion: Zinc plus probiotics therapy is more effective than probiotics alone in reducing the duration of diarrhea, shortening hospital stay, and improving recovery in children with acute diarrhea.